Stem cell therapy for the treatment of heart failure - Willerson, James (Henry Stewart Talks, 2007)
Heart failure: the problem, Reasons for increased heart failure, Current medical treatment of Congestive Heart Failure with systolic dysfunction, Stem cells in the future treatment of heart failure, Stem cell reservoirs, Types of stem cells currently under study